2021
DOI: 10.24191/ajue.v17i2.13403
|View full text |Cite
|
Sign up to set email alerts
|

Relationship of Academic Performance and Academic Self-Concept with Career Decision-Making among UPM Undergraduate Students

Abstract: Choosing the right career paths relevant to their future is probably one of the most challenging decisions confronting the majority of adolescents. Hence, recognition of the factors affecting students’ career decisions is more important than ever. This study aimed to investigate the effects of academic performance and academic self-concept in relation to career decision-making among UPM undergraduate students. A quantitative research design using a questionnaire was utilised. The questionnaire, one touching on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 42 publications
0
3
0
3
Order By: Relevance
“…Beberapa peneliti menggunakan instrumen yang telah ada, seperti Career Decision-Making Difficulties Questionnaire (CDDQ) oleh Gati et al, yang dikembangkan tahun 1996 (Duru et al, 2021;Fatimah, 2020;He et al, 2021;Levin et al, 2020Levin et al, , 2022Mills et al, 2020;Natia & Nino, 2020;Rossier et al, 2021), Skala keputusan karir (Career Decision Making Scale; CDM) dirancang oleh Osipow et al pada tahun 1987 (Pordelan & Hosseinian, 2020;Zaini et al, 2021), Career Decision-making Self-Efficacy Questionnaire, CDMSE (He et al, 2021;Natia & Nino, 2020), Career Decision-Making Self-Efficacy Scale-Short Form (CDMSES-SF) yang dikembangkan oleh Betz et al, pada tahun 1996(Cheng & Sin, 2021Duru et al, 2021;Rossier et al, 2021;Zhou et al, 2021), Career Thoughts Inventory dikembangkan oleh Sampson et al, pada tahun 1996 mengukur pemikiran karir negatif yang terkait dengan pemecahan masalah karir dan pengambilan keputusan (Hayden & Osborn, 2020), skala gaya pengambilan keputusan karir diadopsi dari Rivas, et al, (1989), terdiri atas 12 item, dan mengukur tiga gaya: rasional, intuitif, dan bergantung, dan skala efikasi diri pengambilan keputusan (versi singkat diadaptasi dari Carbonero dan Merino ( 2003) digunakan dalam penelitian Álvarez-Justel & Ruiz-Bueno (2021).…”
Section: No Fokusunclassified
“…Beberapa peneliti menggunakan instrumen yang telah ada, seperti Career Decision-Making Difficulties Questionnaire (CDDQ) oleh Gati et al, yang dikembangkan tahun 1996 (Duru et al, 2021;Fatimah, 2020;He et al, 2021;Levin et al, 2020Levin et al, , 2022Mills et al, 2020;Natia & Nino, 2020;Rossier et al, 2021), Skala keputusan karir (Career Decision Making Scale; CDM) dirancang oleh Osipow et al pada tahun 1987 (Pordelan & Hosseinian, 2020;Zaini et al, 2021), Career Decision-making Self-Efficacy Questionnaire, CDMSE (He et al, 2021;Natia & Nino, 2020), Career Decision-Making Self-Efficacy Scale-Short Form (CDMSES-SF) yang dikembangkan oleh Betz et al, pada tahun 1996(Cheng & Sin, 2021Duru et al, 2021;Rossier et al, 2021;Zhou et al, 2021), Career Thoughts Inventory dikembangkan oleh Sampson et al, pada tahun 1996 mengukur pemikiran karir negatif yang terkait dengan pemecahan masalah karir dan pengambilan keputusan (Hayden & Osborn, 2020), skala gaya pengambilan keputusan karir diadopsi dari Rivas, et al, (1989), terdiri atas 12 item, dan mengukur tiga gaya: rasional, intuitif, dan bergantung, dan skala efikasi diri pengambilan keputusan (versi singkat diadaptasi dari Carbonero dan Merino ( 2003) digunakan dalam penelitian Álvarez-Justel & Ruiz-Bueno (2021).…”
Section: No Fokusunclassified
“…Conseguir una calificación de sobresaliente (9-10) en la asignatura de Educación Física influye positivamente en la mayoría de escalas de Autoconcepto Físico y de actitudes y percepciones respecto a la disciplina de educación física. La nota puede ser una herramienta para valorar el proceso de los alumnos/as, especialmente ya que refleja el nivel de consecución de las competencias u objetivos establecidas en el currículo (Zulaika, 2005;Alcaide, 2020;Camuñas & Alcaide, 2020;Gracia, 2020;Infantes, 2021;Mansilla-Chacón, 2021;Rebolledo-Mejía et al, 2021;Obed Amoah et al;Mohd Zaini et al, 2021). Asimismo, es asombroso que en la mayoría de las titulaciones las puntuaciones adquiridas en educación física estén por encima del 8 ¿Cómo se califica en educación física?…”
Section: Discussionunclassified
“…Indeed, some questions appear to concentrate on evaluations of performance, like "I am able to get a good grade in my science class. " Nevertheless, we believe this result to be useful because it suggests that when students experience successes, their chances of developing interest, and eventually career interests, could be positively influenced (Timothy, 2014;Mohd Zaini et al, 2021), possibly especially at specific periods in life (crossroads) in which students have to decide to pursue or not. Interest has been showed to play an important part in decision at these specific momenta, more than when this tension is relaxed or can still be postponed.…”
Section: End-term Marks and Interest In Stem Careersmentioning
confidence: 98%
“…Numerous studies exist regarding career interest and its relation to different factors as out-of-school time activities (Dabney et al, 2012;Kong et al, 2014); gender (Sadler et al, 2012;Peel et al, 2018); family involvement (Japashov et al, 2022) and school environment (Hazari et al, 2013). Only limited number of studies focus on career interest and its correlation with end-term marks (Timothy, 2014;Mohd Zaini et al, 2021;Japashov et al, 2022). Japashov et al (2022) reported a strong and positive connection of students' career interest with their end-term marks in their quantitative study.…”
Section: Students' Career Interest and End-term Marksmentioning
confidence: 99%